1996
DOI: 10.1007/s004649900162
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of laparoscopic bile duct injuries by intraoperative ultrasonography

Abstract: In cases of iatrogenic occlusion of the bile duct involving hemoclips (including transection or excision between clips), LIOU is a potentially useful modality that may allow earlier recognition and repair. Further studies are needed to evaluate the efficacy of LIOU in detection of bile duct injuries that do not involve hemoclips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…LICU has been suggested to be faster, less expensive, and more sensitive for detecting common bile duct (CBD) stones than FIOC [18]. Other reported advantages of LICU include the ability to visualize vascular anatomy and the potential to assess for bile duct injuries [2,7]. A disadvantage of LICU is that it is not as good at defining detailed ductal anatomy as FIOC [18].…”
mentioning
confidence: 98%
“…LICU has been suggested to be faster, less expensive, and more sensitive for detecting common bile duct (CBD) stones than FIOC [18]. Other reported advantages of LICU include the ability to visualize vascular anatomy and the potential to assess for bile duct injuries [2,7]. A disadvantage of LICU is that it is not as good at defining detailed ductal anatomy as FIOC [18].…”
mentioning
confidence: 98%
“…Interest in laparoscopic ultrasound as an alternative has been increasing. The anatomy of the bile ducts can be demonstrated, and it has been shown to be of potential use in detecting bile duct injury [2].…”
mentioning
confidence: 99%
“…There have also been encouraging results showing that this technique allows the recognition of bile-duct injuries involving clips [5].…”
Section: Discussionmentioning
confidence: 96%
“…Despite use of IOC, diagnosis and repair is significantly delayed in the majority of patients with laparoscopic bile-duct injuries, resulting in less favorable outcomes [1,2]. It has already been demonstrated that, in cases of iatrogenic injuries involving hemoclips, laparoscopic intraoperative ultrasound (LIOU) is a potentially useful modality for proper recognition of these inflicted injuries [5]. However, in the investigation mentioned above, some lesions, like partial lacerations or injuries that do not involve clips, were not studied.…”
Section: Introductionmentioning
confidence: 99%